2014
DOI: 10.1152/jn.00617.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical interference of posture on movement: evidence from Alexander technique teachers rising from a chair

Abstract: While Alexander technique (AT) teachers have been reported to stand up by shifting weight gradually as they incline the trunk forward, healthy untrained (HU) adults appear unable to rise in this way. This study examines the hypothesis that HU have difficulty rising smoothly, and that this difficulty relates to reported differences in postural stiffness between groups. A wide range of movement durations (1–8 s) and anteroposterior foot placements were studied under the instruction to rise at a uniform rate. Bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…Because the two sets of instructions we used had markedly different effects on postural sway, alignment, and movement smoothness, we conclude that the effects were not due to attention to the body, per se , or even solely to the increase in standing height. These results are consistent with previous results indicating that long-term training in the AT improves subtle control of axial tone and of coordination between the legs and torso, 21,51 and they suggest that how one conceives of postural uprightness affects how one stands and moves, and that this influence can be harnessed for rehabilitative purposes.…”
Section: Discussionsupporting
confidence: 92%
“…Because the two sets of instructions we used had markedly different effects on postural sway, alignment, and movement smoothness, we conclude that the effects were not due to attention to the body, per se , or even solely to the increase in standing height. These results are consistent with previous results indicating that long-term training in the AT improves subtle control of axial tone and of coordination between the legs and torso, 21,51 and they suggest that how one conceives of postural uprightness affects how one stands and moves, and that this influence can be harnessed for rehabilitative purposes.…”
Section: Discussionsupporting
confidence: 92%
“…However, muscle length changes may also evoke involuntary shortening reactions (compliant posture behavior) or elicit postural adjustments of other “remote” muscles not being primarily stretched (Andrews et al, 1972 ; Gurfinkel et al, 1989b ). A dynamic “postural frame,” that is inherently incorporated in posture and movement coordination, may account for the resistive or compliant behavior of the body (Cacciatore et al, 2014 ). In this respect, Bernstein's ( 1940 ) interpretation of muscle tone seems more functional, as the degree of readiness for movement related to movement as a state is related to an action, or as a precondition is related to an effect.…”
Section: Conceptual Framework and Approaches For Investigating Postumentioning
confidence: 99%
“…Training in the Alexander Technique has been shown to increase dynamic postural muscle tone [ 21 ], and improve movement coordination and balance [ [22] , [23] , [24] ]. These movement and balance changes are thought to result from the altered postural tone [ 25 ]. Research studies, often using qualitative methods, have reported improvements in psychological well-being, mood and confidence, as well as reduction in performance-related anxiety following one-to-one Alexander lessons [ [20] , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%